2010
DOI: 10.1111/j.1600-0463.2010.02665.x
|View full text |Cite
|
Sign up to set email alerts
|

The highly leukotoxic JP2 clone of Aggregatibacter actinomycetemcomitans: evolutionary aspects, epidemiology and etiological role in aggressive periodontitis

Abstract: For many years, attention has been given to the oral bacterium Aggregatibacter actinomycetemcomitans, as a species possibly implicated in the etiology of aggressive periodontitis in adolescents. One of the major virulence factors of A. actinomycetemcomitans is the leukotoxin which is able to kill important cells of the immune system. As demonstrated in population genetic analyses, the population structure of A. actinomycetemcomitans is mainly clonal with evolutionary lineages corresponding to the serotypes. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(93 citation statements)
references
References 461 publications
(793 reference statements)
3
87
1
2
Order By: Relevance
“…In concordance, this study demonstrated that the presence of A. actinomycetemcomitans was 32.5%. Similar to P. gingivalis, this microorganism also showed statistical association with higher PD, CAL and BOP, corroborating the results of Takeuchi et al At this time, A. actinomycetemcomitans is mostly viewed as opportunistic bacteria of the resident oral microbiota, while its specific JP2 clone, representing serotype b, has properties of a true exogenous pathogen (Haubek, 2010).…”
Section: Discussionsupporting
confidence: 77%
“…In concordance, this study demonstrated that the presence of A. actinomycetemcomitans was 32.5%. Similar to P. gingivalis, this microorganism also showed statistical association with higher PD, CAL and BOP, corroborating the results of Takeuchi et al At this time, A. actinomycetemcomitans is mostly viewed as opportunistic bacteria of the resident oral microbiota, while its specific JP2 clone, representing serotype b, has properties of a true exogenous pathogen (Haubek, 2010).…”
Section: Discussionsupporting
confidence: 77%
“…Unfortunately there is no animal model available for studying the virulence mechanisms of leukotoxin because of its specificity against defense cells of human or old world monkey origin. However, the strong correlation between presence of highly leukotoxic (JP2-clone) A. actinomycetemcomitans and development of attachment loss in adolescents indicates an important role of leukotoxin in the pathogenesis of aggressive periodontitis (Haubek, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Clonal diversity analysis of JP2-like isolates have shown that all strains of this clone have a common ancestor from Northern Africa (Haubek et al, 2007). The high accumulation of this clone in subjects of African origin has indicated a possible host tropism, but could also be a result of the strict vertical transmission pattern of this bacterium Haubek 2010). The expression of leukotoxin is also regulated by environmental factors, such as growth conditions and substrates (Kachlany et al, 2010).…”
Section: Expression and Secretion Of A Actinomycetemcomitans Leukotoxinmentioning
confidence: 99%
See 2 more Smart Citations